Pengaruh Penggunaan Abu Bata Merah Sebagai Filler Pada Aspal Porus Terhadap Karakteristik Marshall - Yunus, Idayani; Sakura, Royanna; Zuraihan (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Almuslim, 2024)
Roads are an important infrastructure for the community in mobilizing. Therefore, it needs special attention in terms of safety and comfort. In several parts of Indonesia, during the rainy season, especially in North Aceh District, Lhoksukon often experiences flooding and the water inundates the roads. This disrupts road users and mobilization. Porous asphalt is a flexible pavement which has excellent advantages for countries with tropical climates such as our country, Indonesia. The advantages of porous asphalt are planned to have large cavities so that they can absorb water freely. In this study the authors will examine the use of red brick ash as a filler obtained at a brick factory in Blang Panjoe Village, Peusangan District, Bireuen Regency. The varying levels of brick ash as filler in porous asphalt mixtures are 0%, 30% and 50%. Furthermore, the determination of KAO and the manufacture of porous asphalt mixing specimens were carried out with red rock ash as a filler substitute of 0%, 30% and 50%. The maximum percentage variation in brick ash content was obtained at 50% substitution with a stability value of 591 kg, a yield value of 3.27 mm, MQ 181.26 kg/mm and VIM 18.8%. The results of the research on the stability and flow values and the Marshall parameters meet the AAPA specifications.